A retrospective study on clinical profile and outcome of dengue fever admitted in a tertiary care center - G J Haridharshan; Vijay K Kulkarni; Gautam Kabbin (Wolters Kluwer Medknow Publications, 2017)
Background: India is among the countries reporting regular outbreaks of Dengue infection. Present study describes clinical profile and outcome of dengue cases. Objective: To study the clinical profile and outcome of dengue fever in pediatric age group using WHO fluid management guidelines (2012). Methods: It is a retrospective observational study of 6 months. All dengue patients admitted during the outbreak from Nov 2015 to May 2016 were included in the study. After clinical assessment, they were investigated and classified according to WHO classification of dengue. Serial monitoring for clinical and hematological parameters was done. Intravenous fluids were administered according to WHO guidelines along with supportive management. Statistical evaluation of the various clinical parameters was done using p value estimation. Final outcome were studied and described. Results: Fever, pain abdomen and vomiting were found to be most common presenting symptoms. Thrombocytopenia was found in 94 % cases and leukopenia in 67.4% cases. Shock was present in 34% patients and average time taken for shock reversal was 2 days. Hepatitis (48.5), AKI (29.7%) and encephalitis (6.2%) were the main complications. Survival rate was 99.4% with mortality being one patient (0.6%). Conclusion: Liver and renal involvement is more common in dengue than previously reported. A high index of suspicion in endemic areas was important .Fluid management played a vital role and helped in recovery.. Early assessment of shock and use of central venous catheterization for fluid resuscitation has shown good outcome.